Kakovost življenja pri dermatoloških boleznih na primeru luskavice - Zupanič, Kaja (Placebo, 2025)
Dermatological diseases, particularly chronic conditions such as psoriasis, have a signifi cant impact on patients' quality of life. Psoriasis not only aff ects the skin, but also often causes itching, pain, and hinders the performance of daily activities. In addition to physical symptoms, psychological and social consequences such as anxiety, depression, feelings of shame, and stigmatization are also common. To better understand these eff ects, standardized questionnaires are used, allowing for a comprehensive assessment of quality of life and supporting the planning of a personalized therapeutic approach. The disease can have a negative impact on personal relationships, work effi ciency, leisure time and social life. Similar to other chronic dermatological conditions, such as atopic dermatitis or vitiligo, the impact of the disease is strongly dependent on individual experience and perception. The article emphasizes the importance of comprehensive treatment, which includes both physical and psychosocial aspects of care for patients with psoriasis.
Keywords: dermatological diseases; dermatološke bolezni; kakovost življenja; Luskavica; psoriasis; quality of life; questionnaires; vprašalniki